A Digest of Acts of Assembly, Relating to the Incorporated District of the Northern Liberties; and of the Ordinances for the Government of the District, at 101-02, Gun Cotton, § 1 (1847) - (:unkn) unknown (General Publisher, 1847)
That no gun-cotton shall be introduced in Philadelphia, nor placed in storage therein, in greater bulk or quantity in any one place, than is permitted by existing laws, with regard to gunpowder; and that all the fines, penalties and forfeitures imposed by an act entitled “An act for securing the city of Philadelphia, and the neighborhood thereof, from damage by gunpowder,”
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER